A influência dos parâmetros radiométricos na eficiência da ação antimicrobiana da PDT com o fotossensibilizador Protoporfirina IX - Dias, Elisabete Cristina (2016)
Conventional antimicrobial strategies are becoming ineffective due to the resistance of pathogenic microorganisms to the drugs, triggering the need to explore treatments and alternative approaches to control these infections. This work is a controlled laboratory test, whose objective is to evaluate the efficacy of aPDT with the photosensitizer PpIX for inactivation of C. albicans as a function of the radiant photon energy. The experiments were carried out in two stages: in the first stage, the same total energy of the LEDs were maintained at the wavelengths: 630 nm, 570 nm, 520 nm and 440 nm during the 60 s, 120 s, 240 s and 480 s (The number of photons emitted by each wavelength will be different due to its energy). In the second step, the same amount and photon flux will be maintained for all wavelengths: 630 nm, 570 nm, 520 nm and 440 nm during the 240s, 480s and 960s times. (Different total energy). PpIX proved to be a very efficient photosensitizer capable of generating sufficient reactive oxygen species and inducing the death of C. albicans in a significant way. The evaluation of the results showed that the greater the flow of photons, the greater the antimicrobial action of PDT with PpIX, since it generates a greater amount of ROS, resulting in a greater efficacy in the elimination of C. albicans. In this way, when the wavelength is longer, photon energy will be lower. So the red photon has less energy than a blue photon and more photons are needed in the red spectral region to produce the same radiant energy as the blue spectral region. Inactivation of microorganisms by PDT is a promising alternative to the use of conventional fungicides and can be used both to control localized fungal infections and to eliminate pathogenic species from the environment. In conclusion, the evaluation of the results showed that the higher the number of photons, the greater the antimicrobial action of PDT with PpIX, as expected.